Artificially ambiguous genetic code confers growth yield advantage - Pezo, V. (National Academy of Sciences, 2004)
A primitive genetic code is thought to have encoded statistical, ambiguous proteins in which more than one amino acid was inserted at a given codon. The relative vitality of organisms bearing ambiguous proteins and the kinds of pressures that forced development of the highly specific modern genetic code are unknown. Previous work demonstrated that, in the absence of selective pressure, enforced ambiguity in cells leads to death or to sequence reversion to eliminate the ambiguous phenotype. Here, we report the creation of a nonreverting strain of bacteria that produced statistical proteins. Ablating the editing activity of isoleucyl-tRNA synthetase resulted in an ambiguous code in which, through supplementation of a limited supply of isoleucine with an alternative amino acid that was noncoding, the mutant generating statistical proteins was favored over the wild-type isogenic strain. Such organisms harboring statistical proteins could have had an enhanced adaptive capacity and could have played an important role in the early development of living systems.